Different DNA-binding specificities of NLP and NIN transcription factors underlie nitrate-induced control of root nodulation. Issue 7 (7th April 2021) - Nishida, Hanna; Nosaki, Shohei; Suzuki, Takamasa; Ito, Momoyo; Miyakawa, Takuya; Nomoto, Mika; Tada, Yasuomi; Miura, Kenji; Tanokura, Masaru; Kawaguchi, Masayoshi; Suzaki, Takuya
Abstract: Leguminous plants produce nodules for nitrogen fixation; however, nodule production incurs an energy cost. Therefore, as an adaptive strategy, leguminous plants halt root nodule development when sufficient amounts of nitrogen nutrients, such as nitrate, are present in the environment. Although legume NODULE INCEPTION (NIN)-LIKE PROTEIN (NLP) transcription factors have recently been identified, understanding how nodulation is controlled by nitrate, a fundamental question for nitrate-mediated transcriptional regulation of symbiotic genes, remains elusive. Here, we show that two Lotus japonicus NLPs, NITRATE UNRESPONSIVE SYMBIOSIS 1 (NRSYM1)/LjNLP4 and NRSYM2/LjNLP1, have overlapping functions in the nitrate-induced control of nodulation and act as master regulators for nitrate-dependent gene expression. We further identify candidate target genes of LjNLP4 by combining transcriptome analysis with a DNA affinity purification-seq approach. We then demonstrate that LjNLP4 and LjNIN, a key nodulation-specific regulator and paralog of LjNLP4, have different DNA-binding specificities. Moreover, LjNLP4–LjNIN dimerization underlies LjNLP4-mediated bifunctional transcriptional regulation. These data provide a basic principle for how nitrate controls nodulation through positive and negative regulation of symbiotic genes. Abstract : Different DNA-binding specificities of LjNLP4 and LjNIN underlie LjNLP4-mediated positive or negative regulation of symbiotic gene expression in nitrate-induced control of nodulation.